NUT Midline Carcinoma Presenting With Bilateral Ovarian Metastases. (March 2015) - Dragoescu, Ema; French, Christopher; Cassano, Anthony; Baker, Sherman; Chafe, Weldon
<x xml:space="preserve">Abstract</x> Nuclear protein of the testis (NUT) midline carcinoma (NMC) is an uncommon, relatively recently characterized carcinoma, which is defined by NUT gene rearrangements. We are reporting a case of NMC in a 38-year-old female who presented with pleural effusion and bilateral ovarian masses. We also discuss some of the difficulties encountered by the practicing pathologist in reaching the diagnosis and the role of ancillary studies. Immunohistochemical staining using a commercially available monoclonal antibody showing nuclear expression of the NUT protein is diagnostic of NMC. Dual-color split-apart fluorescence in situ hybridization (FISH) or reverse transcription polymerase chain reaction (RT-PCR) can be used to characterize the fusion gene, whether BRD4-NUT or BRD3-NUT, or NUT-variant.